2021
DOI: 10.1212/nxi.0000000000001020
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic BK Virus-Specific T-Cell Treatment in 2 Patients With Progressive Multifocal Leukoencephalopathy

Abstract: ObjectiveProgressive multifocal leukoencephalopathy (PML) is a devastating demyelinating opportunistic infection of the brain caused by the ubiquitously distributed JC polyomavirus. There are no established treatment options to stop or slow down disease progression. In 2018, a case series of 3 patients suggested the efficacy of allogeneic BK virus-specific T-cell (BKV-CTL) transplantation.MethodsTwo patients, a bilaterally lung transplanted patient on continuous immunosuppressive medication since 17 years and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 13 publications
0
21
0
5
Order By: Relevance
“… 244 As BKV and JC virus are closely related and share several immunogenic proteins, adoptive transfer of allogeneic JC-STs or BKV-STs has also been explored as treatment of PML. 49 , 65 , 76 78 , 86 Preliminary, albeit very promising, results of those trials demonstrated safety of the infusion of partially matched VSTs as well as alleviation of clinical symptoms, progressive decline of viral load in cerebrospinal fluid and an unprecedented survival beyond 1 year in a number of PML patients with poor expectation for survival. 49 , 65 , 76 78 , 86 …”
Section: Extending the Use Of Psts Beyond The Transplant Settingmentioning
confidence: 99%
“… 244 As BKV and JC virus are closely related and share several immunogenic proteins, adoptive transfer of allogeneic JC-STs or BKV-STs has also been explored as treatment of PML. 49 , 65 , 76 78 , 86 Preliminary, albeit very promising, results of those trials demonstrated safety of the infusion of partially matched VSTs as well as alleviation of clinical symptoms, progressive decline of viral load in cerebrospinal fluid and an unprecedented survival beyond 1 year in a number of PML patients with poor expectation for survival. 49 , 65 , 76 78 , 86 …”
Section: Extending the Use Of Psts Beyond The Transplant Settingmentioning
confidence: 99%
“…Dies widerspricht den Berichten anderer Gruppen, deren Präparate sich von oben erwähnten dadurch unterscheiden, dass sie aus CD4+und CD8+Zellen bestehen, was bedeutsam sein könnte. Verträglichkeit und teilweise beeindruckende klinische Erfolge mit third-party Virusantigen-spezifischen T-Zellen werden berichtet 34 35 36 37 . Für die Wirkung adoptiver T-Zell-Präparate sind beim Empfänger eine Lymphopenie, Immunsuppression zum Zeitpunkt des Transfers, danach aber Freiheit von T-Zell-aktivitätssupprimierenden Medikamenten 38 Voraussetzung.…”
Section: Zelltherapie Gegen Covidunclassified
“…Dies widerspricht den Berichten anderer Gruppen, deren Präparate sich von oben erwähnten dadurch unterscheiden, dass sie aus CD4 + und CD8 + Zellen bestehen, was bedeutsam sein könnte. Verträglichkeit und teilweise beeindruckende klinische Erfolge mit thirdparty Virusantigen-spezifischen T-Zellen werden berichtet [34][35][36][37]. [39][40][41][42] oder an paramagnetischen Partikeln gekoppelter MHC-Peptid-Multimere [43,44], wobei sich wegen ihrer MHC-Unabhängigkeit erstere Methode klinisch stärker etabliert hat.…”
Section: Zelltherapie Gegen Covidunclassified
“…Only one patient experienced mild IRIS, and none had transplantation‐related adverse events. 60 , 61 , 62 , 63 , 64 , 65 Thus, allogenic T‐cell transfer appears to be a promising therapeutic strategy in PML related to refractory immunosuppression. However, virus‐specific T‐cell allogenic transfer requires an infrastructure and a technical expertise that are available at only few centers.…”
Section: Restoration Of Immunity As a Treatment For Pmlmentioning
confidence: 99%